Interventions that facilitate sustainable jobs and have a positive impact on workers' health: an overview of systematic reviews - Michelle M. Haby; Evelina Chapman; Rachel Clark; Luiz A. C. Galvão
ABSTRACT Objective To identify interventions that facilitate sustainable jobs and have a positive impact on the health of workers in health sector workplaces. Methods This overview utilized systematic review methods to synthesize evidence from multiple systematic reviews and economic evaluations. A comprehensive search was conducted based on a predefined protocol, including specific inclusion criteria. To be classified as "sustainable," interventions needed to aim (explicitly or implicitly) to 1) have a positive impact on at least two key dimensions of the integrated framework for sustainable development and 2) include measures of health impact. Only interventions conducted in, or applicable to, health sector workplaces were included. Results Fourteen systematic reviews and no economic evaluations met the inclusion criteria for the overview. The interventions that had a positive impact on health included 1) enforcement of occupational health and safety regulations; 2) use of the "degree of experience rating" feature of workers' compensation; 3) provision of flexible working arrangements that increase worker control and choice; 4) implementation of certain organizational changes to shift work schedules; and 5) use of some employee participation schemes. Interventions with negative impacts on health included 1) downsizing/restructuring; 2) temporary and insecure work arrangements; 3) outsourcing/home-based work arrangements; and 4) some forms of task restructuring. Conclusions What is needed now is careful implementation, in health sector workplaces, of interventions likely to have positive impacts, but with careful evaluation of their effects including possible adverse impacts. Well-evaluated implementation of the interventions (including those at the pilot-study stage) will contribute to the evidence base and inform future action. Interventions with negative health impacts should be withdrawn from practice (through regulation, where possible). If use of these interventions is necessary, for other reasons, considerable care should be taken to ensure an appropriate balance between business needs and human health and well-being.